Implementasi Istighosah Dalam Menanamkan Nilai-Nilai Keagamaan Siswa SMK Takhasus Al-Qur’an Wonosobo - Latif Khusmawardi; Nurul Mubin; Ahmad Robihan (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research aims to: 1) Understand the concept of implementing Istighosah SMK Takhassus Al Qur'an Wonosobo in instilling religious values ​​in its students; 2) knowing the implementation of Istighosah in instilling religious values ​​in students at Takhasus Al Qur'an Vocational School, Wonosobo; 3) To find out the supporting and inhibiting factors. This research uses qualitative field methods to examine complex and dynamic problems. This method was chosen so that data obtained from sources through direct interviews could be filtered more naturally and produce scientific answers. The results of this research show that Takhasus Al-Qur'an Vocational School applies the concept of Istighosah as an effort to instill religious values ​​and religious character in students. This program requires all students to take part in Istighosah activities which are held every day before learning begins. Takhasus Al-Qur'an Vocational School holds Istighosah as a means to foster spiritual awareness and instill religious values ​​in its students. Through this program, it is hoped that students will be able to integrate these values ​​in their daily lives. In instilling religious values ​​through istighosah activities, there are supporting and inhibiting factors for the implementation of Istighosah in instilling students' religious values. The successful implementation of Istighosah to instill religious values ​​in students is supported by good cooperation between teachers, adequate facilities and infrastructure, as well as a supportive environment so that the cultivation of religious characters can continue to be integrated into students' daily lives. There are several obstacles that hinder the effective implementation of Istighosah to instill religious values ​​in Takhasus Al-Qur'an Vocational School students, including students' limited understanding of Istighosah, lack of self-control, and lack of habit in carrying out Istighosah prayers.